?ON SOME DISTRACTING BEHAVIOUR OF AUTOMATIC X-RAY DIFFRACTOMETER (Biological Sciences - PJSIR, 2000)
Twodistractingsituationshavebeendiscussedwhichwerefaced whileworkingwiththeautomaticXvray-di ffractorneter, Siemens D-500C, These problems, appeared to be, in one case, the result of the climatic conditions and working environments inthelaboratories, whereasthesecondonewasfoundto ariseduetothe specialimpurity emitted by the X-ray tube.